Differential expression of two distinct forms of mRNA encoding members of a dipeptidyl aminopeptidase family. - Wada, K (1992)
We have identified two cDNAs encoding dipeptidyl aminopeptidase-like proteins (DPPXs) in both bovine and rat brains that have different N-terminal cytoplasmic domains but share an identical transmembrane domain and a long C-terminal extracellular domain. In both species, one of the cDNAs encodes a protein (designated DPPX-S) of 803 amino acid residues with a short cytoplasmic domain of 32 amino acids, and the other cDNA encodes a protein (designated DPPX-L) with a longer cytoplasmic domain--the bovine cDNA encodes 92 amino acids and the rat cDNA encodes 88 amino acids. The membrane topology of DPPX-S and -L is similar to that of other transmembrane peptidases, and DPPX-S share approximately 30% identity and 50% similarity with reported yeast and rat liver dipeptidyl aminopeptidase amino acid sequences, suggesting that DPPX is a member of the dipeptidyl aminopeptidase family. DPPX-S mRNA is expressed in brain and some peripheral tissues including kidney, ovary, and testis; in contrast, DPPX-L mRNA is expressed almost exclusively in brain. No transcripts for either form are found in heart, liver, or spleen. In situ hybridization studies show that the two transcripts have different distributions in the brain. DPPX-L mRNA is expressed in limited regions of brain with the highest level of expression in the medial habenula. More widespread expression is seen for DPPX-S mRNA. The differential distribution of mRNAs for the DPPX-S and -L suggests that these proteins are involved in the metabolism of certain localized peptides and that the cytoplasmic domain may play a key role in determining the physiological specificity of DPPX.